1969
DOI: 10.1139/g69-036
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosome Complement of Rabbit Blastocysts in Relation to the Time of Mating and Ovulation

Abstract: Six-day blastocysts were recovered from rabbits mated at various intervals from 0 to 10 hours after an ovulation-inducing injection of chronic gonadotrophin. Ten of eighty or 13% of the blastocysts from animals mated between 6 and 9 hours after injection were triploid in chromosome constitution. When karyotyped, seven of the triploids had an XXY and three an XXX sex chromosome complex. The incidence of chromosome abnormalities at delay intervals from 0 to 4 hours was 5%, approximately. No triploids were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 9 publications
3
23
0
Order By: Relevance
“…There are cytogenetic studies on pre-implantation blastocysts of the rabbit (Shaver and Carr 1967;Austin 1967;Shaver 1970;Hof saess and Meacham 1971;widmeyer and Shaver 1972;Martin and Shaver 1972;Fechheimer and Beatty 1974;Fujimoto et al 1974a), but little has been known on the chromosomes of very early intratubal embryos. This paper describes preliminarily some chromosomal aspects of the intratubal rabbit embryos with an improved double fixation method (Fujimoto et al 1974b), with attention to the effect of superovulation on the chromosomes of rabbit intratubal embryos at the 8-to 16-cell stage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There are cytogenetic studies on pre-implantation blastocysts of the rabbit (Shaver and Carr 1967;Austin 1967;Shaver 1970;Hof saess and Meacham 1971;widmeyer and Shaver 1972;Martin and Shaver 1972;Fechheimer and Beatty 1974;Fujimoto et al 1974a), but little has been known on the chromosomes of very early intratubal embryos. This paper describes preliminarily some chromosomal aspects of the intratubal rabbit embryos with an improved double fixation method (Fujimoto et al 1974b), with attention to the effect of superovulation on the chromosomes of rabbit intratubal embryos at the 8-to 16-cell stage.…”
mentioning
confidence: 99%
“…The effect of exogenous gonadotropins on the chromosome abnormalities of rabbit embryos has been a matter of repeated discussion (Shaver and Carr 1969;Hansen-Melander and Melander 1970;Shaver 1970;Fujimoto et al 1974a;Fechheimer and Beatty 1974). The reported incidence of chromosomal anomalies in rabbit blastocysts to which gonadotropins were not administered ranged from 0 to 1.7% (Shaver and Carr 1969;Widmeyer and Shaver 1972;Fujimoto et al 1974a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyspermy and digyny were reported to be increased significantly due to delayed fertilization in the rabbit (17) and mouse (18). Superovulation with PMSG in mice (12) and hamsters (8) led to an increase in triploidy and was believed to be the result of delayed fertilization (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature (Shaver and Carr 1969, Hansen-Melander and Melander 1971, and Widmeyer and Shaver 1972 has indicated that small rabbit blastocysts have a higher incidence of chromosome abnormalities than normal diploid litter mates. In the present study, fewer cell numbers and lower mitotic indices were observed in the 7 chromosomally abnormal cases (out of 72 blastocysts of late 5 and 6 days, 9.7%).…”
Section: Leukocytementioning
confidence: 99%